NEOTEKTOHENEZ OF KANEVSKY PRIDNIPROVJA BASED ON STRUCTURAL MORPHOMETRY - Tustanovska, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The historical and geological structure of Kanevsky dislocations based on the analysis of structural and morphometric maps were retraced and confirmed. Analysis gave detailed maps to set phasic neotektohenezu, trace levels of terraced valleys of the Dnieper and. Identify large and small local structures, which are reflected in the forms of relief, enabling detailed luskuvato-sleeve structure Kanevsky dislocations. Establish direct and indirectly link between recent and more ancient geological structures of the modern forms of relief surface.